PERSONALITY CHANGES WITH DEMENTIA FROM THE INFORMANT PERSPECTIVE: NEW DATA AND META-ANALYSIS. (16th November 2018) - Terracciano, A; Islam, M; Mazumder, M; Schwabe-Warf, D; Stephan, Y; Sutin, A
Abstract: We examined changes in personality in individuals with mild cognitive impairment (MCI) or dementia as observed by family members using both new data and a meta-analysis of the published literature. Similar to past studies, we obtained current and retrospective personality assessments of individuals with MCI or dementia by family informants (n = 50). In the new sample, the five major dimensions (neuroticism, extraversion, openness, agreeableness, and conscientiousness) and facets of personality were assessed using the first-half NEO Personality Inventory-3. In the new sample and meta-analysis (18 samples; n =542) we found consistent changes in personality from the premorbid to current state in patients with cognitive impairment. The largest changes (>1 SD) were declines in conscientiousness (particularly for the facets of self-discipline and competence) and extraversion (decreased energy and assertiveness), as well as increases in neuroticism (increased vulnerability to stress). The new sample suggested that personality changes were larger in individuals taking cognition-enhancing medication (cholinesterase inhibitors and/or memantine). More recent studies and those that examined individuals with MCI found smaller effects. Despite the large systematic mean-level changes, test-retest coefficients remained moderate to high, which suggest that individual differences in personality are relatively maintained, at least at the stage of dementia examined in this study. In conclusion, and consistent with the clinical criteria for the diagnosis of dementia, the new study and meta-analysis found replicable evidence for large changes in personality among individuals with MCI or dementia.